PENGARUH RASIO PENGENCERAN BERBEDA TERHADAP KUALITAS SPERMA IKAN NILEM (Osteochillus hasselti) YANG DISIMPAN DALAM EKSTENDER SARI KURMA, SUSU DAN KUNING TELUR - Dewi Wisudyanti; Laela Fitri; Marhaendro Santoso; Anandita Ekasanti; Emyliana Listiowati; Dewi Nugrayani (Universitas Muhammadiyah Gresik, 2022)
The purpose of this research was to determine the quality of spermatozoa of Nilem Fish (Osteochillus hasselti) after storage in extender palm juice, milk and egg yolk with different dilution ratios. The treatment given was in the form of different dilution ratios between sperm and extender palm juice, milk and egg yolk, namely P1: dilution ratio 1:10, P2: dilution ratio 1:15 and P3: dilution ratio 1:20. The data obtained were analyzed by means of variance (ANOVA). Data that showed a significant effect were continued with further Duncan testing. The results showed that the treatment had a significant effect on motility and viability, but did not have a significant effect on fertility and hatchability.